Construção de patent landscapes como estratégia para identificação de cenários na pesquisa científica e tecnológica - Santos, Ivan José Santana (2020)
In the Life Sciences, major investments are necessary for the development of innovative products and processes. The protection of such technologies through patents is a key step for the commercialization and recovery of investments. Consequently, most of the promising technologies are disclosed in patent documents, which become an important source of technical-scientific-business information. The present work aimed to carry out Patent Landscapes analyses as a way to assess technical-scientific scenario of two technological areas: phosphatidylinositol-3-kinase inhibitors (PI3K), a promising class of molecules for the treatment of some types of cancers; and veterinary vaccines against the main infectious diseases that affect cattle, pigs and birds. Furthermore, PI3K inhibitors had the data obtained from the patent documents compared and complemented with data from clinical trials. In the study of veterinary vaccines, patent documents with greatest potential for high value and quality were also assessed. The Patent Landscapes allowed to analyze the technical features of patent objects, the assignees profiles, the countries that lead the technological development and the main markets of the products evaluated. Finally, this work also presents a Technical Booklet in order to disseminate the use of Patents as a source of information in Scientific Research among the academic community. We hope that the results obtained shed light on the technological and patent scenario, as well as contribute to driving research in these two technological areas. Moreover, we hope that the information presented here can encourage the use of patents as a source of information and the conduct of routine prospective studies in other technological areas. Keywords: Patent Landscape. Technological Forecasting. PI3K inhibitors. Veterinary vaccines.